The Chikungunya Virus nsP3 Macro Domain Inhibits Activation of the NF-κB Pathway - Grace C. Roberts; Nicola J. Stonehouse; Mark Harris (Viruses)
The role of the chikungunya virus (CHIKV) non-structural protein 3 (nsP3) in the virus lifecycle is poorly understood. The protein comprises three domains. At the N-terminus is a macro domain, biochemically characterised to bind both RNA and ADP-ribose and to possess ADP-ribosyl hydrolase activity—an enzymatic activity that removes ADP-ribose from mono-ADP-ribosylated proteins. As ADP-ribosylation is important in the signalling pathway, leading to activation of the transcription factor NF-κB, we sought to determine whether the macro domain might perturb NF-κB signalling. We first showed that CHIKV infection did not induce NF-κB activation and could not block exogenous activation of the pathway via TNFα, although TNFα treatment did result in a modest reduction in virus titre. In contrast, ectopic expression of nsP3 was able to inhibit both basal and TNFα-mediated NF-κB activation, and this was dependent on the macro domain, as a mutation previously shown to disrupt ADP-ribose binding and hydrolase activity (D10A) eliminated the ability to inhibit NF-κB activation. The macro domain D10A mutant also resulted in a dramatic reduction in virus infectivity, consistent with the notion that the ability of the macro domain to inhibit NF-κB activation plays a role in the virus lifecycle.